If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3(4x + -6) = 7 + -5(2x + 1) Reorder the terms: 7 + 3(-6 + 4x) = 7 + -5(2x + 1) 7 + (-6 * 3 + 4x * 3) = 7 + -5(2x + 1) 7 + (-18 + 12x) = 7 + -5(2x + 1) Combine like terms: 7 + -18 = -11 -11 + 12x = 7 + -5(2x + 1) Reorder the terms: -11 + 12x = 7 + -5(1 + 2x) -11 + 12x = 7 + (1 * -5 + 2x * -5) -11 + 12x = 7 + (-5 + -10x) Combine like terms: 7 + -5 = 2 -11 + 12x = 2 + -10x Solving -11 + 12x = 2 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -11 + 12x + 10x = 2 + -10x + 10x Combine like terms: 12x + 10x = 22x -11 + 22x = 2 + -10x + 10x Combine like terms: -10x + 10x = 0 -11 + 22x = 2 + 0 -11 + 22x = 2 Add '11' to each side of the equation. -11 + 11 + 22x = 2 + 11 Combine like terms: -11 + 11 = 0 0 + 22x = 2 + 11 22x = 2 + 11 Combine like terms: 2 + 11 = 13 22x = 13 Divide each side by '22'. x = 0.5909090909 Simplifying x = 0.5909090909
| 28=6c-8 | | 3e-2=12.4 | | 8p=46.4 | | 8(x-4)=24 | | 3(a+2)=30 | | 9e-8=28 | | -3(4-5x)=-42 | | Log(x-1)=0 | | (x+8)+(x+15)=9x+40 | | y^4+2y^2-4=3 | | y^4+2y^2-4=0 | | y^4+2y^2-4=y-3 | | .125+.05+.53= | | 4x+10=3x-12 | | 149-2x=34x+17 | | -92-7=7x+20 | | 24-8x-5=6 | | 2x-3=-8 | | -45x+5y=-50 | | 6n+15=9n+27 | | 3n+5=77-69n | | 4n-9=3n-1 | | 6n+9=n+34 | | 3+5n=15*2n | | 132-2n=4n | | 3n+10=8n | | n(7)=25(2n) | | (5x-1)2=0.64 | | Y-14=31 | | Y-14=10 | | x^2-8x+9=4x-2 | | x^2-3x-5= |